2018
DOI: 10.3390/biomedicines6030082
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Involvement of the Master Transcription Factor NF-κB in Cancer Initiation and Progression

Abstract: Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) is responsible for the regulation of a large number of genes that are involved in important physiological processes, including survival, inflammation, and immune responses. At the same time, this transcription factor can control the expression of a plethora of genes that promote tumor cell proliferation, survival, metastasis, inflammation, invasion, and angiogenesis. The aberrant activation of this transcription factor has been observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
122
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 168 publications
(124 citation statements)
references
References 199 publications
(278 reference statements)
1
122
0
1
Order By: Relevance
“…It has been widely reported that lncRNAs are potential crucial regulators of inflammatory signaling, including NF-κB pathway [31]. NF-κB is a significant contributor to initiation and progression of various cancers via controlling tumor cell proliferation, survival, migration, inflammation, invasion and angiogenesis [32]. Also, NF-κB pathway was reported to facilitate ESCC cell proliferation and invasion [33].…”
mentioning
confidence: 99%
“…It has been widely reported that lncRNAs are potential crucial regulators of inflammatory signaling, including NF-κB pathway [31]. NF-κB is a significant contributor to initiation and progression of various cancers via controlling tumor cell proliferation, survival, migration, inflammation, invasion and angiogenesis [32]. Also, NF-κB pathway was reported to facilitate ESCC cell proliferation and invasion [33].…”
mentioning
confidence: 99%
“…Previous studies also suggest that ACHP exhibited cytotoxicity in adult T-cell leukemia and multiple myeloma cells by interfering with NF-κB signaling [65,67]. The activation of NF-κB, in addition to controlling tumorigenesis [68][69][70][71][72], plays a key role in the induction of fibrosis and ACHP displayed strong antifibrotic effects by suppressing the TGFβ1-induced differentiation of fibroblasts into myofibroblasts and collagen synthesis [73]. Recently, ACHP has been reported to block NF-κB signaling in mouse and human keratinocytes and inhibit multiple sources of cutaneous inflammation in mouse skin [74].…”
Section: Discussionmentioning
confidence: 97%
“…The major molecular target affected by butein treatment in most of the diseases investigated is the transcription factor nuclear factor κB (NF-κB) (Padmavathi et al, 2017). Over the last decade, NF-κB became a major target in drug discovery due to its key role in cancer development, cell proliferation and survival, inflammation, and immune responses (Ahn et al, 2007;Sethi et al, 2008;Sethi et al, 2009;Orlikova et al, 2012;Sethi et al, 2012;Shin et al, 2014;Li et al, 2015b;Monisha et al,2016;Monisha et al, 2017;Ningegowda et al, 2017;Pires et al, 2018;Mohan et al, 2018;Puar et al, 2018). Hence, in this study we aimed to evaluate the effect of butein on NF-κB and its regulated gene products in OSCC cells.…”
Section: Introductionmentioning
confidence: 99%